Performance of Graphene-Reinforced Dental Materials in Restorative and Prosthodontic Applications: A Systematic Review: Graphene in Restorative and Prosthodontic Materials - Naeem, Maria; Yasin, Sharqa; Azam, Ambreen; Pasha, Mehwish; Manzoor, Kinza; Qazi, Zunaira (Pakistan Journal of Health Sciences, 2026)
Mechanical fatigue, marginal degradation, microbial biofilm formation, and low long-term durability are persistent challenges associated with dental restorative and prosthodontic materials. The integration of graphene and its variants is an effective approach to enhance the structural and biological properties of conventional dental biomaterials. Objective: To systematically evaluate the performance of graphene-reinforced dental materials in restorative and prosthodontic applications. Methods: This systematic review was performed in accordance with PRISMA-2020 guidelines and involved searches of PubMed/MEDLINE, Scopus, and Cochrane Library to identify original research published between January 2019 and March 2025. Sixteen original in-vitro studies examining graphene-modified dental materials were included. Case reports, reviews, and animal studies were excluded. Meta-analysis was not performed due to substantial heterogeneity in graphene types, concentrations, base materials, and outcome measures. Narrative synthesis of data was performed on mechanical, physical, antimicrobial, and biocompatibility results. Results: Sixteen original in-vitro studies were included. Graphene derivatives, mainly graphene oxide and graphene nanoplatelets, were incorporated into resin composites, PMMA denture base materials, glass ionomer cements, dental adhesives, and CAD/CAM polymers. The majority of studies exhibited improved flexural strength, hardness, fracture resistance, and antimicrobial properties against Streptococcus mutans and Candida albicans. However, higher concentrations of graphene in certain formulations resulted in increased surface roughness and a lower degree of conversion. Conclusions: Graphene-reinforced dental materials exhibit promising mechanical reinforcement and antimicrobial properties in laboratory settings. However, formulation-dependent trade-offs and the lack of long-term clinical data necessitate further standardized experimental and clinical investigations before routine clinical adoption.